Improved performance of the cryptographic key distillation protocol of an FSO/CV-QKD system on a turbulent channel using an adaptive LDPC encoder - López-Leyva, Josué Aarón; Arvizu Mondragón, Arturo; Santos Aguilar, Joel; Ramos García, Raúl (My University, 2017)
In this paper, a dynamical and adaptive LDPC coding scheme is proposed in order to improve the performance of the cryptographic key distillation protocol of an FSO/CV-QKD system considering the atmospheric turbulence levels that may be present in the classic channel. In this scheme, the Generator and Parity-check matrices of the encoder are modified according to the Rytov variance values estimated in the classical channel in order to improve the final secret key rate of the QKD system. The simulation results show that the final secret key was incremented 87.5 Kbps (from 52.5 Kbps to 140 Kbps) using the adaptive code rate; meaning that the information encrypted and transmitted is increased. In addition, the use of the dynamical encoder avoids the drastically reduction of the final secret key rate when the conditions of the classical channel are considered. Our proposal might be implemented based on the use of high-speed FPGA’s and DSP’s commercially available.
Revista Mexicana de Física
Keywords: Atmospheric turbulence; Secret key rate; Rytov variance; Mutual information